Decline of Amateur Lepidoptera Collectors Threatens the Future of Specimen-Based Research. (13th January 2021) - Fischer, Erica E; Cobb, Neil S; Kawahara, Akito Y; Zaspel, Jennifer M; Cognato, Anthony I
Abstract: Amateur butterfly and moth collectors in the United States have procured more Lepidoptera specimens than professional scientists. The advent of large government-supported database efforts has made a quantitative examination of the impact of amateur collecting of these insects possible. We reviewed trends in Lepidoptera collecting since 1800, using more than 1 million United States lepidopteran specimens that have been collected into public databases. Our findings show a steep rise in the collection of specimens after World War II, followed by a short plateau and sharp decline in the late 1990s. In contrast, the rate of observations submitted to database groups dramatically increased around 2005. Declining acquisition of Lepidoptera specimens may compromise critically important testing of contemporary and future ecological, conservation, and evolutionary hypotheses on a grand scale, particularly given documented declines in insect populations. We suggest that increasing collaboration between professional and community-based scientists could alleviate the decline in amateur-collected specimens.